Ultrasonic-assisted immersion of parboiled treatment improves head rice yield and nutrition of black rice and provides a softer texture of cooked black rice - Xin Wu; Yi Zhou; Qun Lu; Rui Liu (Ultrasonics Sonochemistry, 2023)
Parboiling is gaining increasing attention as it can enhance the head rice yield (HRY) and nutritional quality of non-pigmented rice. The traditional parboiling process with high-temperature immersion requires a long immersion period and results in hard texture of cooked parboiled black rice (PBR), which may be addressed by ultrasound-assisted immersion. In this study, we evaluated the effect of power, time and temperature of ultrasonic immersion on the HRY, texture profile and nutritional quality of PBR. Proper ultrasound-assisted immersion could increase the HRY by about 20% and the GABA content by up to 133%, as well as reduce the arsenic and cadmium content by up to 61% and 79% relative to untreated black rice (UBR), respectively. Moreover, it could increase the content of essential minerals such as calcium, iron and zinc to some extent, and free and bound polyphenols, despite of a certain loss of anthocyanins. It could also improve the palatability of cooked rice. Furthermore, response surface experiments based on the Box-Behnken design were performed to obtain and validate the optimal conditions of ultrasound-assisted immersion (540 W, 45 min, 57 °C). On this basis, morphological changes might be one reason for the improved HRY, nutrition and texture of PBR compared with those of UBR, namely the disappearance of cracks near the aleurone layer and formation of new cracks in the interior of rice.